2015
DOI: 10.1530/erc-15-0042
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in endocrine tumors

Abstract: Autophagy is an important intracellular process involving the degradation of cytoplasmic components. It is involved in both physiological and pathological conditions, including cancer. The role of autophagy in cancer is described as a 'double-edged sword,' a term that reflects its known participation in tumor suppression, tumor survival and tumor cell proliferation. Available research regarding autophagy in endocrine cancer supports this concept. Autophagy shows promise as a novel therapeutic target in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 78 publications
0
13
0
1
Order By: Relevance
“…14 That is the reason why we investigated the effect of miR-18a on autophagy. As shown in Figure 5a, overexpression of miR-18a-5p significantly induced GFP/mRFP-LC3 dot accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…14 That is the reason why we investigated the effect of miR-18a on autophagy. As shown in Figure 5a, overexpression of miR-18a-5p significantly induced GFP/mRFP-LC3 dot accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not clear whether there is a crosstalk between PI3K/AKT/mTOR/p70S6K and MAPK/ERK pathway to regulate autophagy, it has been suggested that RAS protein might be involved in the intersection of MAPK/ERK and PI3K/AKT signaling pathways. RAS stimulates autophagy when the MAPK signaling pathway is activated, while inhibits autophagy when PI3K/AKT is activated (Furuta et al 2004, Morani et al 2014, Netea-Maier et al 2015, Weckman et al 2015. Whether an alternative pathway, involved in the TSHinduced activation of p70S6K in normal cells, may play a role in autophagy induction in thyroid cells, need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it appears that autophagy is in a mutual relation with the process of apoptosis, and that this interconnection is context-dependent; it has been shown that autophagy may facilitate apoptosis or necrosis (Marino et al 2014). Therefore, autophagy has been exploited as a possible therapeutic strategy (O'Reilly et al 2006, Amaravadi et al 2016 in different tumor models, including glioma, glioblastoma, neuroblastoma and breast cancer, and in some NEN models (Amaravadi et al 2007, Degtyarev et al 2008, Fan et al 2010, Xu et al 2011, Hong et al 2013, Seitz et al 2013, Weckman et al 2015. Chloroquine (CQ), commonly used in the treatment of malaria and of rheumatic autoimmune disorders, inhibits lysosomal hydrolase activity and consequently autophagy.…”
Section: :6mentioning
confidence: 99%